Menakar Independensi Hakim Pengadilan Pajak Pasca Putusan MK Nomor 10/PUU-XVIII/2020 - Ananthia Ayu Devitasari (The Constitutional Court of the Republic of Indonesia, 2021)
Judicial independence is the main foundation for the of justice and legal certainty. Regarding the discourse on the independence of judicial power, the Constitutional Court decided on Case Number 10/PUU-XVIII/2020 which examined Article 5 paragraph (2) and Article 8 paragraph (2) of Law Number 14 of 2002 concerning the Tax Court. The Petitioners challenged the authority of Ministry of Finance to develop the organization, administration and finance for the Tax Court, the authority of the Minister of Finance to propose the chairperson and deputy chairman of the Tax Court. Furthermore, the Court in its ruling states that “the Chairperson and Deputy Chairperson are appointed by the President who is elected from and by the Judges who are subsequently proposed through the Minister with the approval of the Chief Justice of the Supreme Court for 1 (one) term of office for 5 (five) years”. This study examined the independence of the tax court judges after the Constitutional Court Decision Number 10 / PUU-XVIII / 2020 with independent judicial theory approach. This study showed that the Court’s decision not only supports the independence of the tax court judges but also draws a demarcation line between judicial power and executive power.